CHARACTERISTICS OF DESIGN SOLUTIONS IN TECHNICAL CREATIVITY - Dzhurayeva Mokhira Ravshanovna (American Journals Publishing, 2023)
This article talks about the specific features of design solutions in technical creativity. The author clarified the problem on the basis of existing scientific and historical literature, relying on cultural information and written sources. Comparative analysis of existing unique approaches and theories on the specific features of design solutions in technical creativity.
Keywords: Creativity, design, art, aesthetics and artistry, artist, designer.